ESG disclosure and sustainable financial performance: The moderating role of corporate reputation - Sari, Rafika; Safdar , Muhammad; Sakti, Eklamsia (Universitas Muhammadiyah Yogyakarta, Indonesia, 2026)
Research aims: This study aims to investigate the impact of ESG disclosure on sustainable financial performance (SFP) and to examine the moderating role of corporate reputation. Design/Methodology/Approach: This study uses quantitative methods and secondary data sources. The study sample comprised 210 data companies reporting ESG on Bloomberg. The analysis technique uses logistic regression with IBM SPSS Statistics 25 as the statistical tool.Research Findings: ESG disclosures are associated with significant negative effects on sustainable financial performance (SFP). The interaction between ESG disclosures and a company's reputation is positive and statistically significant. However, these effects operate in a negative baseline relationship, suggesting that reputation weakens the negative impact of ESG disclosures rather than reinforces its positive impact.Theoretical contribution/Originality: This study explores the under-researched ESG–SFP link in emerging markets, addresses ongoing debates, and introduces corporate reputation as a novel moderating variable, highlighting its role in shaping ESG disclosure’s impact on sustainable financial performance.Practitioner/Policy implication: Practitioners should integrate ESG disclosure with reputation management to enhance sustainable financial performance, while policymakers in emerging markets should design frameworks that encourage transparent ESG reporting and recognize corporate reputation as a strategic driver of financial sustainability. Limitations/Research Implication: This study is limited to one country and sector, limiting generalizability. Sustainable financial performance is simplified as a binary profit–risk measure, while corporate reputation relies on a market-based proxy that may not capture broader reputational dimensions.